Engineering Proceedings The 7th International Conference on Time Series and Forecasting - Rojas, Ignacio; Rojas, Fernando; Javier Herrera, Luis; Pomares, Hector; Rojas, Ignacio; Rojas, Fernando; Javier Herrera, Luis; Pomares, Hector (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The ITISE 2021 (7th International conference on Time Series and Forecasting) seeks to provide a discussion forum for scientists, engineers, educators, and students about the latest ideas and realizations in the foundations, theory, models, and applications for interdisciplinary and multidisciplinary research encompassing disciplines of computer science, mathematics, statistics, forecaster, econometric, etc., in the field of time series analysis and forecasting.
English
Keywords: Technology: general issues; T1-995; History of engineering & technology